(untitled) (Indian Journal of Arid Horticulture, 2025)
Micropropagation techniques of cactus pear for a thorn-less, vegetable type elite genotype, which was collected under germplasm collection programmes, was developed successfully through single bud explant. Physiologically mature buds on cladodes were collected and single bud segment was used for culture initiation. Maximum multiple shoots (8 shoots/ explant) formation was achieved on MS medium supplemented with 30 g sucrose, 8 g agar and 2 mg 6- Benzylaminopurine (BA) 0.1 mg alpha-Naphthalene acetic acid (NAA) per liter. Multiple shoot clump were further subjected to culture for shoot elongation medium devoid of plant growth regulators. The elongated shoots were rooted cent per cent under in vitro conditions. The rooted plantlets were successfully acclimatized under three step hardening procedure. Under in vitro conservation study, in vitro rooted plantlets were used for further conservation by reducing growth of the plantlets and by minimizing sub-culturing process. The rooted plantlets were transferred on agar solidified MS medium supplemented with activated charcoal 3 g/l and different combinations of BA (0, 0.5, 1.0 mg/l) and NAA (0, 0.5, 1.0 mg/l). The higher concentration of BA (1.0 mg/l) was found to increase shoot proliferation and was detrimental to root growth of the in vitro plantlets whereas higher concentration of NAA (1.0 mg/l) was found to influence both shoot and root growth positively. This technique of in vitro conservation was found effective in maintaining cultures continue for more than six years. Further, proliferated growth of in vitro maintained plantlets were harvested and transferred to new containers for increasing number of stock materials.